Advances in transforming kudzu (pueraria phaseoloides) and carrot (daucus carota var. danvers 126) roots with different agrobacterium rhizogenes strains for increasing ma fungi growth (2002)
Kudzú (P. phaseoloides) and carrot (D. carota) roots were transformed in this survey into different kinds of culture medium by using five different A. rhizogenes strains. These presented different behaviour both in carrot transformation by A. rhizogenes 15834, A.r.8196 and A.r.2659 strains as well as kudzu transformation by A.r.15834 and A.r.1724 strains. Transformed carrot root growth was increased in WM culture medium, whilst transformed kudzu root growth did not increase in either the same medium or in modified MS medium. Transformed carrot roots were used for G. intrarradices increase and sporulation; however, wild AMF strains, isolated from a mining area (the lower Cauca area of Antioquia), did not grow either in roots from this specie or those from kudzu, in spite of this plant having great affinity for wild AMF strains. The results represent an advance in the procedure for DNA isolation and keeping AMF collections, required for other research.